A coordinate descent method for market equilibrium problems with price groups - O.V. Pinyagina (Учёные записки Казанского университета: Серия Физико-математические науки)
In the present paper, a model of market equilibrium with price groups in the form of variational inequality for a single-product market of an infinitely divisible product has been considered. Unlike the classical model, in which all market participants are equal and a single equilibrium price is found, it is assumed in this paper that each seller or buyer can split the set of his/her counterparties into non-overlapping groups and assign a certain price function to each group. For this model, the equilibrium conditions have been formulated and proved. The conditions for the existence of a solution to the problem, based on the coercivity property, have been also proposed and justified.